The Role of Parents in Appliying Discipline to Children in A Pandemic Period - Melfia, Irena Dara (Prosiding University Research Colloquium, 2021)
In this era of the COVID-19 pandemic, children are learning online. Therefore, all children activities are also carried out at home, so parents certainly have a big role in studentactivitiesat home,oneofwhichisdiscipline.Disciplineis anaspectthat mustbe instilled in children from an early age so that later they can get used to ituntil adulthood.Withoutdiscipline,thechildwill become someone who has no direction and purpose. Therefore, discipline is very important to be instilled. In this study,the subjects usedwere parentsand children.The purpose ofthis research is to findoutthe role of parentsinapplyingdisciplinetochildren.Thedatacollectionmethodusedisin theform of a literature study. Therefore, data is obtained about the role of parents in applying discipline to children inthe pandemic era.